2020
DOI: 10.1101/2020.04.28.20082446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiometabolic risk factors and preclinical target organ damage among adults in Ghana: Findings from a national study

Abstract: Background: Sub Saharan Africa (SSA) has the highest prevalence of cardiovascular diseases (CVD). Nevertheless, very few studies have directly examined the development of and risk factors for CVD among Africans. Objective: To examine CVD risk factors and outcomes particularly in the early stage of CVD development among adults in Ghana. Methods: Using a stratified multistage random sampling method, 1,106 participants were recruited as a nationally representative sample of the general population ≥18 years in G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…These results are consistent with reports from a Ghanaian study [55]. Cigarette smoking was generally uncommon in our study, but the impact of "Shesha pipe smoking" among young age must be evaluated.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with reports from a Ghanaian study [55]. Cigarette smoking was generally uncommon in our study, but the impact of "Shesha pipe smoking" among young age must be evaluated.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 93%
“…In this study, elevated TG (22.1%) was the most prominent form of dyslipidemia, followed by an elevated LDL-C and HDL-C, with women having the highest prevalence of all measures of dyslipidaemia in comparison to men. This observed pattern of dyslipidaemia prevalence in our study is similar to a survey conducted in Ghana [55] but inconsistent with results documented by Asiki and team [56] and Gebreegziabiher et al [57], where the most prevalent dyslipidaemia markers were HDL-C, TC and LDL-C. Despite the observed disparities in the different measures of dyslipidaemia, studies have reported a high prevalence of all forms of dyslipidaemia among women [58][59][60][61].…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 65%
“…Cardiovascular diseases are one of the most important causes of death in the world, and their pathogenesis is such that they are affected by several risk factors such as obesity, diabetes and hypertension. 1 Increased serum uric acid levels can lead to endothelial dysfunction resulting in atherosclerosis by releasing reactive oxygen species and is reported as one of the risk factors for cardiovascular diseases. 2 In the process of purine decomposition, uric acid is the final product.…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out, however, that other unhealthy factors besides high BP such as ethnicity, age, gender, type 2 diabetes mellitus, obesity, sleep apnea syndrome, and renal disease contribute to the development of HMOD and cardiovascular events. 4 Moreover, it deserves to be emphasized that BP is dynamic physiologic variable characterized by large short-and long-term variations (ie, beat-to-beat, over 24 hours, day-to-day, and visit-to-visit). From a physiological point of view, these BP changes substantially reflect an adaptive response to a variety of physical and mental stimuli aimed at preserving the cardiovascular homeostasis.…”
mentioning
confidence: 99%
“…Although cardiac and extracardiac complications of hypertension increase markedly with exposure to increasing BP load, the prognostic value of BP values routinely assessed in clinical practice still remains unsatisfactory regardless of the methods used. It should be pointed out, however, that other unhealthy factors besides high BP such as ethnicity, age, gender, type 2 diabetes mellitus, obesity, sleep apnea syndrome, and renal disease contribute to the development of HMOD and cardiovascular events 4 . Moreover, it deserves to be emphasized that BP is dynamic physiologic variable characterized by large short‐ and long‐term variations (ie, beat‐to‐beat, over 24 hours, day‐to‐day, and visit‐to‐visit).…”
mentioning
confidence: 99%